Private residence at 99 High Street, general view, Brookline, Massachusetts. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
Exterior view of a residence located at 99 High Street, Brookline, Massachusetts.; Caption on image: Residence-99 High St. (2) Ext, gen. view.; Binder Number 4. Pocket Number: 1.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.